Creating Drama with 7-11 Year Olds : Lesson Ideas to Integrate Drama into the Primary Curriculum. - Tandy, Miles; Howell, Jo., 1972- (David Fulton Publishers, Taylor & Francis Group [distributor], 2009)
This highly practical guide gives you all the ideas you need to make drama an exciting, regular and integral part of your primary school's curriculum. -- Provided by publisher.